Sensitive analysis of fatty acid esters of hydroxy fatty acids in biological lipid extracts by shotgun lipidomics after one-step derivatization - Hu, Changfeng (Anal Chim Acta, 2020)
Branched fatty acid esters of hydroxy fatty acids (FAHFAs) are an important family of endogenous lipids, possessing antidiabetic and anti-inflammatory functions. Therefore, analysis of FAHFAs in biological samples obtained under healthy and disease states can uncover underlying mechanisms of various relevant disorders (e.g., diabetes and autoimmune diseases). Up to now, due to their extremely low abundance, the determination of the changed levels of these species is still a huge challenge, even though great efforts have been made by utilizing liquid chromatography-tandem mass spectrometry with or without derivatization. Herein, we described a novel method for analysis of FAHFAs present in lipid extracts of biological examples after solid-phase extraction and chemical derivatization with one authentic FAHFA specie as an internal standard based on the principles of multi-dimensional mass spectrometry-based shotgun lipidomics. The approach possessed marked sensitivity, high specificity, and broad linear dynamic range of over 3 orders without obvious matrix effects. Moreover, after chemical derivatization, the molecular masses of FAHFAs shift from an overlapped region with ceramide species to a new region without overlaps, removing these contaminating signals from ceramides, and thereby reducing the false results of FAHFAs. Finally, this novel method was successfully applied for determining FAHFAs levels in varieties of representative biological samples, including plasma from lean and overweight/obese individuals of normoglycemia, and tissue samples (such as liver and white adipose tissue from diabetic (db/db) mice). We revealed significant alterations of FAHFAs in samples under patho(physio)logical conditions compared to their respective controls. Taken together, the developed method could greatly contribute to studying altered FAHFA levels under a variety of biological/biomedical conditions, and facilitate the understanding of these lipid species in the patho(physio)logical process.